ANALISIS KINERJA PORTOFOLIO SAHAM PADA EMITEN PASAR SAHAM SAAT PANDEMI COVID-19: Studi Kasus Saham Sektor Farmasi - Christy Dwita Mariana (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2022)
The purpose of this research is to examine the performance of a stock’s portfolio using the favorite strategy from Indonesian investor, Momentum invest strategy in examining a momentum that happened because of the Covid-19 pandemic. Sample from this research are using 5 different stocks that have abnormal return throughout Covid-19 pandemic that happen in Indonesia. Portfolio sampling test from 6 months before the Covid-19 pandemic being announced and 6 months after the Covid-19 pandemic being announced. The methods that been used are Abnormal Return, Index Sharpe, and also t-Test: Paired two Sample for Means in regards to validate the comparison. There are 2 Portfolio strategies, consist of 2 periods: Formation period and ownership period to test the momentum that happened. The outcome of this research is to prove that there is momentum and strategy efficiency in investment momentum when particular event happened in Indonesia Stock Exchange.